COMPARATIVE EVALUATIONS OF POLYMERIZATION SHRINKAGE OF LIGHT CURING COMPOSITE RESINS - Sonia Florentina Cotinghi; Lucian Toma Ciocan; Vlad Gabriel Vasilescu; Marian Miculescu; Marina Imre (Romanian Journal of Oral Rehabilitation)
Aim of the study Composite resins are a class of dental materials widely used in dentistry. This paper aims to present the most important general aspects related to dental composites, focusing on the effects of the polymerization reaction. Materials and methods for this purpose, the rate of shrinkage after photopolymerization was tested and measured for composite materials from two different manufacturing companies. Results The results obtained in the present study compare the linear shrinkage between different light-curing composite materials, this being attributed to the consistency and composition of the material, information provided by the manufacturer. These results are indicative for the clinician and can guide his choice depending on the clinical situation Conclusions The idea of an ideal material, which meets all the requirements of clinicians and can be integrated into the complexity of the human body, seems a difficult goal to achieve, but through the continuous development of technology and science, more and more sustainable results can be achieved in time.